2021
DOI: 10.1097/wad.0000000000000439
|View full text |Cite
|
Sign up to set email alerts
|

Subtle Changes in Medication-taking Are Associated With Incident Mild Cognitive Impairment

Abstract: Introduction: Medication-taking is a routine instrumental activity of daily living affected by mild cognitive impairment (MCI) but difficult to measure with clinical tools. This prospective longitudinal study examined in-home medication-taking and transition from normative aging to MCI. Methods: Daily, weekly, and monthly medication-taking metrics derived from an instrumented pillbox were examined in 64 healthy cognitively intact older adults (Mage=85.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…Lastly, no association between objective pillbox variables and cognitive performance was seen in this study despite prior findings demonstrating that MCI individuals often open their pillbox later in the day and have a more variable daily first time of pillbox opening compared to CN older adults. 19 Prior work demonstrated that among those with executive dysfunction, the complexity of daily life routines interacts with cognition to predict medication management in older adults. 38 Therefore, a shift toward more structured and simpler routines with reduced executive demands during the COVID-19 pandemic may have reduced group differences in these metrics and contributed to divergent findings.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Lastly, no association between objective pillbox variables and cognitive performance was seen in this study despite prior findings demonstrating that MCI individuals often open their pillbox later in the day and have a more variable daily first time of pillbox opening compared to CN older adults. 19 Prior work demonstrated that among those with executive dysfunction, the complexity of daily life routines interacts with cognition to predict medication management in older adults. 38 Therefore, a shift toward more structured and simpler routines with reduced executive demands during the COVID-19 pandemic may have reduced group differences in these metrics and contributed to divergent findings.…”
Section: Discussionmentioning
confidence: 99%
“…Outcome variables were the nine continuous sensor variables that have demonstrated group differences between CN and MCI individuals. [17][18][19][20][21] The Benjamini-Hochberg procedure with the Stats_PADJUST extension for SPSS was utilized to correct for multiple comparisons with a false discovery rate set at 0.10.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations